FRI0156 An antimicrobial mechanism, netosis, is potentially involved in ankylosing spondylitis pathogenesis. (12th June 2018) - Ruiz-Limon, P.; Castro, M.C.; Lopez-Pedrera, C.; Abalos-Aguilera, M.C.; Barbarroja, N.; Perez-Sachez, C.; Arias-de la Rosa, I.; Ortega, R.; Font, P.; Gonzalez-Reyes, J.A.; Villalba, J.M.; Lopez-Medina, C.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease, of unknown etiology, that mainly affects the axial skeleton and the sacroiliac joints in the pelvis. Neutrophils are critical actors in innate immunity and their activation has been involved in the progression of AS symptoms. Recently, NETosis has been suggested to play a central role in several pathologic states, including rheumatology diseases. Nevertheless, this process has not been described yet in AS patients Objectives: 1) To evaluate and characterise the presence of NETosis in AS patients. 2) To explore the relationship among NETosis markers and clinical characteristics of this disease Methods: Thirty patients with AS and 32 healthy donors (HD) were included in the study. Disease activity was determined by BASDAI index and, CRP and ESR levels; in parallel, inflammatory markers were determined in plasma by ELISA kits. Spinal mobility of AS patients was measured by the BASMI index, and structural damage was calculated by the mSASSS index. Ex vivo, spontaneous NETosis generation in purified neutrophils from AS patients and HDs were measured by fluorescence (n=6) and scanning electron (n=3) microscopy after 6 hour of incubation. PMA, known to promote NETosis, was used as positive control. DNA extrusion was analysed by fluorescence microscopy and fluorimetry after SYTOX staining, whereas elastase percentage (NE) was analysed by fluorescence microscopy after staining of neutrophils with NE antibody. In vivo, mieloperoxidase (MPO) and NE protein expression were measured by flow cytometry (FACSCalibur), whereas extracellular DNA was examined in plasma using fluorimetry after SYTOX staining Results: Compared to HDs, AS neutrophils showed spontaneous extracellular release of a meshwork of DNA nuclear and granule proteins (NETs), as demonstrated by fluorescence microscopy, fluorimetry, and scanning electron microscopy. Indeed, analysis of DNA fibres staining by SYTOX revealed that NETosis rate was above baseline levels after 6 hour of ex vivo AS neutrophil incubation as compared to those from HDs (p < 0.05). Furthermore, higher cell free-DNA levels were observed between AS patients and HDs at 6 hour (p<0.05). Increased spontaneous NETs production in this pathology was additionally corroborated by the observation of an enhanced percentage of NE-staining cells after 6 hour of incubation (p < 0.05). In vivo, higher intracellular NE levels (p=0.036), and plasma DNA concentrations (p=0.021) were also found in AS patients as compared to HDs. Correlation studies showed that plasma DNA levels positively correlated with inflammatory markers (i.e. CRP, ESR and TNFα), and with the spinal mobility index BASMI. In addition, a positive correlation was found between intracellular NE levels and plasma IL-1β concentration Conclusions: 1) NETosis is increased in AS patients. 2) Raised NETosis in AS is associated with several markers of inflammation and mobility. Thus, NETosis might act as a key mediator in the etiopathogenesis of AS. Funded by JA PI-0314–2012, SER, ISCIII (RIER RD16/0012/0015) Disclosure of Interest: None declared